THE EFFECT OF THE PROBLEM BASED LEARNING (PBL) MODEL ON STUDENT LEARNING OUTCOMES IN INDONESIAN CULTURAL DIVERSITY MATERIAL CLASS IV SD NEGERI 1 PAGAR AIR - Sari, Intan; Nurmasyitah, Nurmasyitah; Mislinawati, Mislinawati (Elementary Education Research, 2024)
Learning that only focuses on completing material and memorizing concepts makes students unable to develop their thinking patterns so that it has an impact on the learning outcomes obtained by students. Where the learning outcomes obtained by students do not reach the Learning Goal Achievement Criteria (KKTP). The formulation of the problem in this research is "Is there an influence of the Problem Based Learning (PBL) model on student learning outcomes in Indonesian cultural diversity material for class IV SD Negeri 1 Pagar Air Aceh Besar?". This research aims to determine the influence of the Problem Based Learning (PBL) model on student learning outcomes in Indonesian cultural diversity material for class IV SD Negeri 1 Pagar Air Aceh Besar. The approach used in this research is a quantitative approach to the type of research, namely Quasi Experimental Design with a Nonequivalent Control Group Design. This research was conducted in class IV of SD Negeri 1 Pagar Air Aceh Besar which is located in Meunasah Krueng sub-district, Want Jaya District, Aceh Besar Regency. Sampling used a total sampling technique with 31 IVA students as the control class and 29 IVB students as the experimental class. The instrument used in this research was a multiple choice test with 10 questions. The data collection technique uses tests, while the data analysis technique uses SPSS Statistics 26 and hypothesis testing uses the paired sample T-Test. The results of hypothesis testing with the paired sample T-Test statistic obtained a significance value (2-tailed) of 0.000 0.05. So the decision making criteria are H_a accepted and H_0 rejected. Thus, it can be concluded that there is a significant influence of the use of the Problem Based Learning (PBL) model on student learning outcomes in the material on Indonesian cultural diversity in class IV SD Negeri 1 Pagar Air Aceh Besar.